1
$\begingroup$

What is the Laurent series expansion of $e^{-e^{\frac {1} {z}}}$ about $z=0$?

I know that if the Laurent series expansion of a function $f$ about $z=0$ is

$$f(z)= \cdots + \frac {b_2} {z^2} + \frac {b_1} {z} + b_0 + b_1 z + b_2 z^2 + \cdots$$

then $$b_k = \oint_{\gamma} \frac {f(z)} {z^{k+1}}\ dz, \ k \in \Bbb Z.$$ where $\gamma$ is the unit circle centered at the origin.

I also know that if $f$ is entire and if $$f(z)=\sum_{k=0}^{\infty} a_k z^k$$ be the Taylor's series expansion of $f$ about $z=0$ then the Laurent's series expansion of $g(z)=f(\frac {1} {z})$ (which is analytic on $\Bbb C \setminus \{0 \}$) about $z=0$ is $$g(z) = \sum_{k=0}^{\infty} \frac {a_k} {z^k}.$$

Using these facts I have tried to find out the Laurent series expansion for $e^{-e^{\frac {1} {z}}}$ about $z=0$. Clearly in this case the Laurent's series expnsion for $e^{\frac {1} {z}}$ about $z=0$ is $$e^{\frac {1} {z}} = \sum_{k=0}^{\infty} \frac {1} {k! z^k}$$ since we know that Taylor's series expansion of $e^z$ about $z=0$ is $$e^z=\sum_{k=0}^{\infty} \frac {z^k} {k!}.$$ From the above discussion can I conclude that the Laurent's series expansion of $e^{-e^{\frac {1} {z}}}$ about $z=0$ is $$e^{-e^{\frac {1} {z}}} = \sum_{j=0}^{\infty} (-1)^{j}\frac {1} {j!} \left ( \sum_{k=0}^{\infty} \frac {1} {k!z^k} \right )^{j}?$$

If the answer is 'yes' then why? Also I want to know what will be the residue of $e^{-e^{\frac {1} {z}}}$ at $z=0$ where I am really struggling. Please help me in this regard.

Thank you very much.

$\endgroup$
1
$\begingroup$

As you have said that if we know the Taylor series expansion of an entire function $f$ about $z=0$ as lets say $$f(z)=\sum_{k=0}^{\infty} a_k z^k$$ then the Laurent series expansion of $g(z)=f(\frac 1 z)$ about $z=0$ is $$g(z)=\sum_{k=0}^{\infty} \frac {a_k} {z^k}.$$ We use this fact to evaluate the Laurent series expansion of $e^{-e^{\frac {1} {z}}}$ about $z=0$. Let us first find the Laurent series expansion of $f(z)=e^{-e^z}$ about $z=0$. Clearly $f$ thus defined is entire. Hence we can find the Taylor series expansion of $f$ about $z=0$ as follows $:$

$$f(z)=\sum_{k=1}^{\infty} \frac {f^{(k)}(0)} {k!} z^k.$$ where $f^{(k)}(0)$ denotes the $k$-th order derivative of $f$ at $z=0$. If you evaluate the higher order derivatives of $f$ at $z=0$ then you will find that

$$ f^{(k)}(0) = \left\{ \begin{array}{ll} \frac {1} {e} & \quad k = 3n,\ \ \ n \in \Bbb Z^+ \cup \{0 \}\\ {-\frac {1} {e}} & \quad k=3n-2,\ \ \ n \in \Bbb Z^+\\\ 0 & \quad k=3n-1,\ \ \ n \in \Bbb Z^+ \end{array} \right. $$

Hence the Taylor series expansion of $f$ about $z=0$ is $$f(z)=\frac {1} {e}\left (1-z+\frac {z^3} {3!}- \frac {z^4} {4!} + \cdots \right ).$$

Therefore the required Laurent series expansion of $e^{-e^{\frac {1} {z}}}$ about $z=0$ is same as the Laurent series expansion of $g(z)=f(\frac {1} {z})$ about $z=0$ which is $$g(z)=\frac {1} {e} \left (1-\frac {1} {z} + \frac {1} {3! z^3} - \frac {1} {4! z^4} + \cdots \right ).$$

From here you can easily see that the residue of $e^{-e^{\frac {1} {z}}}$ at $z=0$ is $-\frac {1} {e}$.

$\endgroup$
1
  • $\begingroup$ Very helpful. Thank you very much @Arnab Chatterjee. $\endgroup$ – D_C Jun 5 '18 at 7:29
0
$\begingroup$

You are on the right track, but that is not the Laurent expansion (the powers of $z$ are not isolated). \begin{align} e^{-e^{1/z}}&=\sum_{n=0}^\infty\frac{(-1)^n}{n!}\,e^{n/z}\\ &=\sum_{n=0}^\infty\frac{(-1)^n}{n!}\sum_{j=0}^\infty\frac{1}{j!}\frac{n^j}{z^j}\\ &=\sum_{j=0}^\infty\frac{1}{j!}\Bigl(\sum_{n=0}^\infty\frac{(-1)^nn^j}{n!}\Bigr)\frac{1}{z^j}. \end{align} The residue at $z=0$ is the coefficient of $1/z$ ($j=1$), which is $$ \sum_{n=0}^\infty\frac{(-1)^nn}{n!}=\sum_{n=1}^\infty\frac{(-1)^n}{(n-1)!}=-\sum_{n=0}^\infty\frac{(-1)^n}{n!}=-\frac1e. $$

$\endgroup$
4
  • $\begingroup$ I think you have used the fact that the Taylor series of $e^{f(z)}$ about $z=0$ is $\sum\limits_{k=0}^{\infty} \frac {\{f(z) \}^{k}} {k!}$. But we need to prove this result before using it. Isn't it so? $\endgroup$ – D_C Jun 4 '18 at 4:19
  • $\begingroup$ I have used that for any complex number $w$, $e^w=\sum_{n=0}^\infty w^n/n!$. Now let $w=-e^{1/z}$. $\endgroup$ – Julián Aguirre Jun 4 '18 at 14:51
  • $\begingroup$ But how do you make sure that this thing indeed holds good? $\endgroup$ – D_C Jun 5 '18 at 7:28
  • $\begingroup$ What "thing"?${}$ $\endgroup$ – Julián Aguirre Jun 5 '18 at 13:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.